Talking with Your Hands: How Hand Gestures Influence Communication - Cascio Rizzo, Giovanni Luca; Berger, Jonah; Zhou, Mi (Journal of Marketing Research, 2026)
From salespeople and entrepreneurs to politicians and influencers, marketplace actors often communicate with their hands. Yet despite how integral these movements are to communication, little work in marketing has examined their effects. Might moving one's hands while speaking increase persuasion? And if so, what types of movements are more impactful, and why? A multimethod investigation, including automated video analysis of thousands of presentations, application of a large multimodal model on almost 200,000 video segments, and preregistered controlled experiments, demonstrates that hand movement can boost impact. Further, the results demonstrate that certain hand gestures (i.e., illustrators) are particularly impactful. By making content easier to understand, illustrators make speakers seem more competent, which increases persuasion. Taken together, these findings shed light on hand movement's impact, deepen understanding around nonverbal communication, and highlight how automated video analysis and multimodal models can provide insights into consumer behavior.